AI Ethics in ChatGPT Usage Among University Students - Muhammad Abiyyu De Rossi; Rialdo Marcell Sitorus; Riscitta Ogilvie Hubertus Sinaga; Togu Natanael Clarkia Purba (Jurnal Pendidikan dan Sastra Inggris, 2026)
The rapid development of Artificial Intelligence (AI), particularly ChatGPT, has significantly transformed higher education worldwide. University students increasingly use ChatGPT to complete assignments, generate academic ideas, summarize journals, translate texts, and support learning activities. However, alongside its educational benefits, ChatGPT also raises ethical concerns related to plagiarism, academic dishonesty, dependency on AI, declining critical thinking, and data privacy. This study aims to critically review previous studies discussing AI ethics in ChatGPT usage among university students. This research employs a qualitative literature review approach using Norman Fairclough’s Critical Discourse Analysis (CDA) as the primary analytical framework. The data were obtained from scholarly journal articles, academic reports, and previous research published between 2021 and 2025. The findings reveal three dominant discourse themes: ChatGPT as an educational assistant, ChatGPT as a threat to academic integrity, and ChatGPT as a reflection of educational pressure within modern higher education systems. Furthermore, the literature demonstrates that ethical debates regarding ChatGPT are closely connected to broader ideological issues involving technological optimism, neoliberal productivity culture, and institutional authority. This study concludes that AI ethics in higher education is not merely a technical issue but a socially and ideologically contested phenomenon shaped through discourse, educational values, and institutional interests.